EVALUASI USABILITY PADA APLIKASI OSAGA DENGAN MENGGUNAKAN METODE PENGUJIAN USABILITY - Dwika Agatha Putrisa; Suharyadi Suharyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The Salatiga Ojek Application (OSaga) is an application-based transportation service developed as an alternative online transportation option for the people of Salatiga City. Although the application has been used by more than 10 thousand users, various complaints related to its usage still exist, including issues with the map feature, delays in OTP code delivery, and slow application loading times. This study aims to evaluate the usability level of the OSaga application and identify usability problems experienced by users. The research was conducted using the usability testing method combined with interview techniques and the distribution of the System Usability Scale (SUS) questionnaire. The study involved five participants for usability testing and respondents for measuring user satisfaction through SUS. The analysis employed success rate metrics to measure learnability, time-based efficiency to assess efficiency, error rate to determine the level of user errors, and SUS to measure satisfaction. The results showed that the OSaga application achieved a task success rate of 100%, a time-based efficiency value of 0.008 goals/sec, and an error rate value of 0.13. In addition, the average SUS score obtained was 67.12, which falls into Grade C with an adjective rating of “OK” and is categorized within the marginal acceptability range. The findings indicate that the OSaga application has a fairly good level of usability and is usable for users; however, several improvements are still needed, particularly in terms of navigation, system performance, and map feature stability, in order to enhance user comfort and satisfaction more optimally.